Contemporary design in quarantine: A critical review of design responses to Covid-19 crisis - Moura, Monica [UNESP]; Perez, Iana Uliana [UNESP]; Melara, Lucas Furio [UNESP]; Junior, Jose Carlos Magro [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2020)
The following article aims to analyze Brazilian and international cases of design responses to the COVID-19 pandemic related crises. It initiates with reflections about the social and political roles of design, emphasizing the importance of social innovation, design activism, and transition design to contemporary design. The methodological approach adopted is qualitative and quantitative with assessment and selection of data based on the bibliographic, desk, and documentary research methods. The result of 113 mapped cases is presented by graphic synthesis and discussed through the bibliographic research.
Keywords: Contemporary Design; Design Activism; Pandemic; Social Innovation; Transition Design